MANAJEMEN WAKAF PRODUKTIF DALAM MENGEMBANGKAN ASET YAYASAN DI PONDOK PESANTREN WALI SONGO NGABAR PONOROGO TAHUN 2024 - Azizun, wahyu; Arlinta Prasetian Dewi (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2025)
The implementation of a productive waqf management program in developing foundation assets at the Wali Songo Ngabar Ponorogo Islamic Boarding School is very important. Because productive waqf management in developing foundation assets is one of the efforts made for the welfare of the community within the foundation. Therefore, the management of productive waqf must be maintained so that the Institution obtains benefits and advantages for the people within the Foundation. This research aims to: 1) To determine the implementation of productive waqf management at the Wali Songo Islamic Boarding School Ngabar Ponorogo. 2) To find out about the development of productive waqf at the Wali Songo Ngabar Islamic Boarding School. The research results reveal that: 1) The implementation of waqf management at the Ngabar Islamic Boarding School is well managed, namely carried out in accordance with sharia principles and is productive. This can be seen from the management strategy which consists of; planning, organizing, managing human resources, leadership and supervision. 2) Development of Productive Waqf carried out by the Wali Songo Ngabar Islamic Boarding School, namely with several efforts such as development through additional assets through collaboration with third parties, development of assets through purchases from waqf proceeds and development of assets through gifts by new wakifs.